PELATIHAN PENGOLAHAN DATA STATISTIK DENGAN MENGGUNAKAN APLIKASI SPSS BAGI GURU-GURU SMP UNTUK MENUNJANG PENULISAN KARYA ILMIAH - Yacob Ruru; Ida M. Hutabarat; Untung Turua (JURNAL PENGABDIAN PAPUA, 2019)
Training on processing statistical data was carried out on 18 and 25 August 2018 at SMPN 2 Sentani. The aim of the training is to motivate and improve the ability of teachers to process statistical data and interpret their output and be able to use the SPSS Program in processing statistical data so as to improve the quality of research and teacher scientific work. The method used to support the success of this program is in the form of training, demonstration and practice or tutorial. The results of the implementation of service activities felt by the team and the training participants were very satisfying, with indicators of participant activity in each activity process, and participating in training enthusiastically. The training of statistical programs for junior high school teachers in the community service program that has been implemented is expected to provide understanding and also the ability of teachers to use statistical programs that will have an impact on increasing research productivity and teaching and learning and professionalism of teachers in junior high school Jayapura.Keywords: data processing,  statistic, SPSS, SMPN Sentani